Transformasi Digital Sebagai Strategi Kenusantaraan Warisan Budaya: Studi AI Pada Kereta Kencana Paksi Naga Liman - Mahendra Wibawa; Sunarmi Sunarmi; Santosa Soewarlan (MAVIS : Jurnal Desain Komunikasi Visual, 2024)
The purpose of this article is to examine how Artificial Intelligence (AI) using Dall-E, can reinterpret cultural artifacts, providing a new perspective in the visualization and understanding of the history of the Paksi Naga Liman Kencana Train. This research methodology involves collecting data from an etic and emic point of view, which is then used for AI species to produce new visualizations. Apart from that, data collection was also carried out using unstructured interviews with the tour guides on duty. The results of this research produced a number of keywords that can be used as prompts for AI, as well as various examples of visual results produced by AI based on combinations of these prompts. AI can respond to and reinterpret these cultural artifacts, providing new dimensions to the visual experience and historical understanding.